Vitamin D in preventive medicine - Pilz, Stefan; Gaksch, Martin; Ó Hartaigh, Bríain; Tomaschitz, Andreas; März, Winfried (Anticancer research, 2015)
The global burden of vitamin D deficiency is of great concern for public health. Meta-analyses of randomized controlled trials (RCTs) have shown that vitamin D supplementation reduces fractures, falls, and mortality. These findings are, however, not universally accepted and there exists certain controversy regarding the potential benefits of vitamin D. Whereas vitamin D might also be relevant for extra-skeletal diseases such as cancer, cardiovascular diseases, or infections, the recommended Dietary Reference Intakes (DRI) are solely based on skeletal effects. The Recommended Dietary Allowance (RDA) range from 600 to 800 international units (IU) of vitamin D per day, corresponding to a 25-hydroxyvitamin D level of 20 ng/mL (50 nmol/L). Consequently, there exists a substantial gap between the RDA and the actual high prevalence of vitamin D deficiency in general populations, particularly among the elderly. Therefore, achieving the RDA will require additional efforts including food fortification, vitamin D supplementation and health campaigns.